Development and feasibility of a conceptual model for planning individualised physical exercise training (IPET) for older adults: a cross-sectional study - Teljigovic, Sanel; Dalager, Tina; Nielsen, Nina Odgaard; Holm, Lars; Ejvang, Mette Bahn; Sjøgaard, Gisela; Søgaard, Karen; Sandal, Louise Fleng (BMJ open, 2024)
ObjectiveOlder adults constitute a heterogeneous group, and the focus of the individual physical exercise is often subject to the reasoning and experience of health professionals or exercise physiologists who prescribe them. Thus, this is the first effort to explicitly conceptualise the planning of individualised physical exercise training (IPET) for older adults in an outpatient setting and investigate individual exercise preferences.DesignThe concept of IPET was developed by researchers, exercise physiologists and health professionals from a real-life outpatient setting using an iterative approach. Health indicators assessing aerobic capacity, strength, balance and musculoskeletal pain/discomfort sites form the basis of physical exercise recommendations. A cross-sectional study was conducted to assess the basis of implementing IPET.SettingOutpatient setting.ParticipantsWe included 115 older adults (70 females) from an outpatient setting with a median age of 74 years.Outcome measuresHealth indicators assessing aerobic capacity, strength, balance and musculoskeletal pain/discomfort sites were collected and informed the concept of IPET that structures exercise programmes based on the individual citizen’s needs and physical exercise preferences. Exceeding a health indicator cut-point results in exercise content mitigating the risk associated with the health indicator.ResultsWe included 115 older adults (70 females) from an outpatient setting median age of 74 years. Approximately two-thirds of participants exceeded at least one health indicator cut-point for aerobic training. One-third of the participants exceeded the cut-point for upper extremity strength, and almost all participants >99% exceeded the cut-point for lower extremity strength. Approximately two-thirds of the participants exceeded the cut-point for functional/balance training. The most prevalent site of musculoskeletal pain was the lower extremities. Eight of 20 training combinations were used, clustering the 115 participants primarily in three main training combinations.DiscussionThis study shows that older adults vary in physical functioning, indicating that exercise preferences and rehabilitation needs are individual.Trial registration numberNCT04862481.